The improvements of warehouse management and production process at cv. Purezento - Lita Grace Hadyiswanto, Claudya; F. Firman, Aries (The Indonesian Journal of Business Administration, 2016)
Abstract - It is no doubt that creative industry is the wheel for Indonesia’s economic future. However, despite the government support and growth in the creative industry, companies must be able to keep up with the market dynamics. Purezento, as one of the growing companies in the industry, faces a few challenges in this. Purezento encounters problems in its production process and warehouse management. The biggest challenge is the warehouse management where out-of-stock and overstock are the norms in its daily operations. On top of that, the company cannot manage its employees well which is reflected in the productivity level fluctuation. Qualitative research method was used in this paper in order to discover and solve the real problems that hinder Purezento’s production process and warehouse management. The inexistence of knowledge codification is the reason behind Purezento’s problems. The employees do have knowledge but they do not know how to put it in an accessible media. Furthermore, Purezento also employs networked culture and does not have written documents for its rules and regulation that give rise to poor employee engagement. The research gives some recommendations to the company regarding its inventory and workforce management. It suggests the company has 139 lumbers and 213 lumbers for its minimum and maximum standard, respectively. It is also shown that if Purezento can maximize its human resources, the company can save minimum Rp. 210.000,- for the raw material per months and it will be able to avoid Rp. 29.520.000 potential loss the least from its production.                Keywords: Qualitative Research, Production Process, Warehouse Management, Knowledge Management,   Corporate Culture.